Enhancing the Transition Capability of Danish Biomass Technology By Applying a Futures Study Backcasting Methodology on the Biogas Sector. - Lybæk, Rikke; Christensen, Thomas Budde; Kjær, Tyge (European Journal of Sustainable Development, 2013)
This paper discusses how the Danish biogas sector can achieve the political goals set outby the Danish government, in order to turn around the currently weak implementation ofthe technology. Biogas technology provides many environmental and energy relatedbenefits, but the transition capability of the technology has so far not been supported by astable policy pushing the sector in the right direction. The paper argues that a moreholistic and consistent support for the biogas sector must be developed, enhancing itsindependence from shifting Danish policy regimes. This could be achieved by applying abackcasting methodology in combination with future research activities which areidentified by means of energy chain analysis. The paper stresses that future Danish biogasresearch should be applied all along the sector’s energy chain, and not just in parts of it,looking at enhancement of the transition capability within ‘Resources’,‘Technology/Conversion’ and ‘Distribution/End-use’. The future research activities,proposed in this paper are interconnected and thought backwards with the goal ofcreating reachable aims for achieving the political targets set forth before the year 2020and 2050.